When people's judgments of learning (JOLs) are extremely accurate at predicting subsequent recall: the "Displaced-JOL effect". Issue 6 (3rd July 2018) - Bui, Young; Pyc, Mary A.; Bailey, Heather
ABSTRACT: Judgments of learning (JOL) made after a delay more accurately predict subsequent recall than JOLs made immediately after learning. One explanation is that delayed JOLs involve retrieving information about the target item from secondary memory, whereas immediate JOLs involve retrieval from primary memory. One view of working memory claims that information in primary memory is displaced to secondary memory when attention is shifted to a secondary task. Thus, immediate JOLs might be as accurate as delayed JOLs if an intervening task displaces the target item from primary memory, requiring retrieval from secondary memory, prior to making the JOL. In four experiments, participants saw related word-pairs and made JOLs predicting later recall of the item. In Experiment 1, delayed JOLs were more accurate than JOLs made shortly after learning, regardless of whether a secondary task intervened between learning and JOL. In Experiments 2–4, the secondary task demands increased and JOLs made shortly after learning with an intervening task were just as accurate as delayed JOLs, and both were more accurate than immediate JOLs with no intervening task (Experiment 4). These results are consistent with a retrieval-based account of JOLs, and demonstrate that the "delayed-JOL effect" can be obtained without a long delay.